PENGARUH LATIHAN RESISTANCE BAND TERHADAP KETEPATAN TRHEE POINT SHOOTING EKSTRAKURIKULER BOLA BASKET PUTRA SMA NEGERI 1 PALOPO - Sangkanni Maharani Shaadin; Ahmad; Hidayat, Rachmat (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of Resistance Band training on the accuracy of three-point shooting in extracurricular male basketball participants at SMA Negeri 1 Palopo. This study used an experimental method with a one-group pretest-posttest design and involved 30 students as samples taken using a total sampling technique. The instrument used was a three-point shooting accuracy test. The results showed an increase in shooting ability after being given training for six weeks, indicated by an average pretest score of 7.77 increasing to 12.73 in the posttest. Hypothesis testing using a paired sample t-test showed a significance value of 0.001 (p < 0.05), so it can be concluded that Resistance Band training has a significant effect on increasing three-point shooting accuracy. Thus, Resistance Band training is effective to be used as a training method to improve basketball shooting ability in students.